Effect of ginger (Zingiber officinale roscoe) inclusisve diet on testicular disorder in high cholesterol diet-induced obese rats: Involvement of cholesterol pathway. - Seun Funmilola Akomolafe; Isaac Adeola Oriyomi (Elsevier, 2024)
Background: Obesity, which is typically associated with hypercholesterolemia, has become a worldwide problem in recent times, raising alarming concerns on the testicular function in men in countries around the world. Aim: Hence, this study focused at discovering the potency of ginger inclusive diet in correcting testicular disorder in a high cholesterol diet (HCD)-induced obese rat model focusing on cholesterol pathway. Methods: The rodents were split up into seven separate groups (n = 10): healthy rats fed basal diet; obese untreated rats fed HCD; reference drug-treated obese rats, clomiphene citrate (CC, 2 mg/kg BW/day); obese rats fed high cholesterol diet with 2 % raw ginger (RG) inclusion; obese rats fed high cholesterol diet with 4 % RG inclusion; obese rats fed high cholesterol diet with 2 % boiled ginger (BG) inclusion; obese rats fed high cholesterol diet with 4 % BG inclusion for twenty-four weeks. Thereafter, the testosterone level, semen parameters, steroidogenic enzymes, lipid-metabolism related biomolecules, inflammation-related and apoptosis-related markers enzymes expression were assayed using testicular tissue. Result: Result showed that HCD disrupted the semen parameters, and affected testosterone level by causing a down-regulation in the gene expression of steroidogenic enzymes as well as up-regulation in the gene expression of inflammatory and apoptotic markers when compared with healthy control rats. Interestingly, treatment with ginger inclusive diet attenuated these effects with boiled ginger treatment having better results relative to the raw ginger treatment. Conclusion: This study confirms that a diet rich in ginger prevents testicular tissue by modulating the expression of key enzymes involved in inflammation, cholesterol metabolism, apoptosis, and steroidogenesis in HCD-induced obese rats, with boiled ginger possessing the greatest therapeutic benefit in the management of obesity-induced male fertility derangements, even beyond its impact on body weight regulation.